Coagulation Factor XIII and Cardiovascular Disease in UK Asian Patients Undergoing Coronary Angiography - Warner, Darren; Mansfield, Michael W.; Grant, Peter J. (Thrombosis and Haemostasis, 2001)
Possession of the coagulation factor XIII Val34Leu (FXIIIVal34Leu) polymorphism is associated with protection against myocardial infarction (MI) in Caucasians, in the absence of features of insulin resistance. The role of this polymorphism in the UK Asian population, with its high prevalence of insulin resistance and ischaemic heart disease, is unknown. We investigated the frequency of genotypes at this polymorphism, and measures of circulating FXIII in a group of UK Asians attending for coronary angiography. Genotype at the FXIIIVal34Leu polymorphism was not associated with MI. FXIII B-subunit levels correlated with waist: hip ratio (r = 0.19, p 0.005), HbA1c (r = 0.18, p 0.05), fasting triglycerides (r = 0.21, p 0.005), total cholesterol (r = 0.29, p 0.0005) and PAI-1 antigen (r = 0.24, p 0.005). An association between FXIIIVal34Leu and FXIII cross-linking activity was confirmed in these subjects (one-way ANOVA p 0.0005). This evidence does not support the hypothesis that FXIIIVal34Leu is protective against MI in the UK Asian population. FXIII B-subunit levels are strongly linked to risk factors for cardiovascular disease, suggesting an underlying association with insulin resistance.
Keywords: Polymorphism; ethnicity; cardiovascular disease; factor XIII; risk factors